2007
DOI: 10.1179/136485907x229068
|View full text |Cite
|
Sign up to set email alerts
|

The ELISA-based detection of anti-Opisthorchis viverriniIgG and IgG4in samples of human urine and serum from an endemic area of north–eastern Thailand

Abstract: The levels of correlation between the number of Opisthorchis viverrini eggs excreted in the faeces and levels of anti-Opisthorchis IgG and IgG(4) in the serum and urine (as indicated by absorbances in ELISA) have recently been evaluated in north-eastern Thailand. The 225 subjects investigated in detail, all of whom came from an endemic village in Chaiyaphum province, were selected on the basis of the numbers of O. viverrini eggs that they were excreting. ELISA based on a crude antigen extract of the trematode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…Individuals and animals infected with this food-borne trematode show high serum/plasma levels of the classic antibodies associated with helminth infections such as IgG, IgG1, IgG4 and IgE to crude OV antigen extracts. As such, it has been hypothesized that circulating antibodies to OV antigens may “leak” from the plasma into the urine at levels proportionate to the intensity of OV infection [14], [16]. However, as seen in these other studies [14], [16], we found that urine IgG to OV antigen is a poor method for diagnosing OV infection and an even poorer method for predicting the intensity of OV infection (Tables 3 and 4).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Individuals and animals infected with this food-borne trematode show high serum/plasma levels of the classic antibodies associated with helminth infections such as IgG, IgG1, IgG4 and IgE to crude OV antigen extracts. As such, it has been hypothesized that circulating antibodies to OV antigens may “leak” from the plasma into the urine at levels proportionate to the intensity of OV infection [14], [16]. However, as seen in these other studies [14], [16], we found that urine IgG to OV antigen is a poor method for diagnosing OV infection and an even poorer method for predicting the intensity of OV infection (Tables 3 and 4).…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have attempted to show a correlation between the intensity of OV infection and levels of urine IgG to various crude OV antigen extracts [14][16]. Although urine can contain small quantities of ‘intact’ immunoglobulin as well as light and heavy chain fragments of immunoglobulin, the restrictive pore radius of the renal glomerular filter in a healthy human kidney would not filter macromolecules the size of intact IgG (for review see [17]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in humans have shown a close relationship between parasite-specific IgG and intensity of O. viverrini infection [15][17]. Moreover in O. viverrini infections, the level of parasite-specific IgG is correlated to the severity of the clinical disease rather than to the egg counts in stools [16], [18]. Consequently, the detection of specific antibodies has been considered as a complementary tool to establish the definitive diagnosis of this infection [19]–[21].…”
Section: Introductionmentioning
confidence: 99%
“…In past epidemiological surveys, crude extracts of O. viverrini worms – either from the tissues (somatic antigen preparations) and/or the excretory/ secretory products (ES) released by cultured flukes in vitro – have been employed as antigens for serodiagnosis [7,8]. However, preparation of fluke-derived antigens is tedious with maintenance of the O. viverrini parasite in the laboratory and samples of metacercariae to infect laboratory hamsters reliant on natural sources of infected, wild fishes, which are unpredictable and variable depending on the season [9].…”
Section: Introductionmentioning
confidence: 99%